Верифікація контенту в соціальних медіа - Рябічев, Вячеслав Львович (Київський національний університет імені Тараса Шевченка, 2015)
Розглянуто питання перевірки інформації, отриманої з Всесвітньої павутини, в тому числі в умовах інформаційної агресії з боку Російської Федерації протягом 2014-2015 років. Метою дослідження було розробити та обґрунтувати сучасні методи протидії поширенню спотвореної інформації та ворожої пропаганди за допомогою методів контент-аналізу, порівняльного аналізу, повнотекстових пошуків, розпізнавання образів, OSINT-методу (розвідка за відкритими джерелами). На конкретних фактах проаналізовано особливості роботи онлайн-журналіста під час воєнних дій та сучасні цифрові інструменти для пошуку, перевірки, порівняння та аналізу різноманітного контенту. Створено набір правил та запропоновано нові методики для роботи репортера соціальних медіа в умовах інформаційної війни.

The main objectives of the study are: elaboration of the operative algorithm for professional online journalists under information warfare (IW) conditions; analysis of the modern methods and tools for the effective verification of information; application of the decision support systems (DSS) for the content distribution in social media; specification of the set of rules for network reporters to itemize their activity. In this study the issue of verifying the information received from the World Wide Web is analysed, in particular, the information spread during the military aggression of the Russian Federation against Ukraine in 2014–2015. We also present and justify some modern means of counteracting the spread of intentionally distorted information and hostile propaganda. We focus on using content analysis, comparative analysis, full-text searching, pattern recognition, and open-source intelligence (OSINT) method. Through using specific facts and findings we analyse the features of the work of an online journalist during the warfare and modern digital tools for content search, verification, comparison and analysis. The results and conclusions of this investigation allow generalizing and structuring some methods and techniques of content verification. A number of rules and helpful hints for enhancing the efficiency of online journalists are proposed. Current trends in development of social media allow predicting further increase of the Internet audience and consequently an increasing amount of information on the web. With the development of citizen journalism (street journalism) in Ukraine, the significance level of journalistic responsibility for information dissemination in mass media has been constantly increasing. Out of a huge amount of reports and data, a journalist must be able to identify the most accurate and up-to-date ones, check them promptly, and distribute on cross-media platforms. Under such conditions, an online reporter is obliged to possess modern skills of dealing with digital tools for content verification, and to keep in contact with experts whom he can ask for advice.
Content Verification in Social Media
Keywords: verification; social media; social networks; cross-media; Internet journalism; citizen journalism; monitoring; information war; crowdsourcing; верифікація; соціальні медіа; соціальні мережі; крос-медіа; інтернет-журналістика; громадянська журналістика; моніторинг; інформаційна війна; краудсорсинг